1966
DOI: 10.1037/h0022836
|View full text |Cite
|
Sign up to set email alerts
|

Reaction time and serial versus parallel information processing.

Abstract: 2 experiments were conducted in which Ss gave 1 of 3 responses to each stimulus in a random sequence prepared from 32 distinct stimuli which assumed 1 of 2 levels for each of S dimensions. The sequence was constructed so that 2 of the 32 stimuli occurred with probability $ each and the remaining 30 stimuli occurred with probabilities summing to J. Ss were instructed to respond by depressing a -key to one of the high frequency stimuli, and a + key to the other, and a 0 key to any of the remaining 30. Results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1969
1969
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…This research was also supported in part by a grant from the Office of Education to Dr. Howard E. Egeth. produced results which support parallel processing of multidimensional information (Donderi & Zelnicker, 1969;Egeth & Pachella, 1969;Hawkins, 1969;Neisser, 1963;Neisser, Novick, & Lazar, 1963;Shurtleff & Marsetta, 1968;Tulving & Lindsay, 1967). And finally, the remaining studies in this body of research yield results which do not unequivocally support anyone mode of processing (Atkinson, Holmgren, & Juola, 1969;Bamber, 1969;Egeth & Smith, 1965;Lindsay & Lindsay, 1966;Nickerson, 1967;Sekuler & Abrams, 1968).…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This research was also supported in part by a grant from the Office of Education to Dr. Howard E. Egeth. produced results which support parallel processing of multidimensional information (Donderi & Zelnicker, 1969;Egeth & Pachella, 1969;Hawkins, 1969;Neisser, 1963;Neisser, Novick, & Lazar, 1963;Shurtleff & Marsetta, 1968;Tulving & Lindsay, 1967). And finally, the remaining studies in this body of research yield results which do not unequivocally support anyone mode of processing (Atkinson, Holmgren, & Juola, 1969;Bamber, 1969;Egeth & Smith, 1965;Lindsay & Lindsay, 1966;Nickerson, 1967;Sekuler & Abrams, 1968).…”
Section: Previous Researchmentioning
confidence: 99%
“…In some studies alphanumeric characters comprised the stimulus sets (e.g., Neisser et al, 1963;Nickerson, 1966;Sternberg, 1966), while others used randomly generated figures (Briggs & Blaha, 1969;Sekuler & Abrams, 1968). The remaining stimuli can be separated into two types: stimuli formed from combinations of purely arbitrary dimensions which can be added or taken away at will, such as color or inscribed figure (Egeth, 1966;Harris & Haber, 1963;Hawkins, 1969;Lindsay & Lindsay, 1966;Nickerson, 1967), and stimuli whose dimensions are integral to the whole stimulus configuration such that without one of the dimensions the stimulus ceases to exist (Egeth & Pachella, 1969;Tulving & Lindsay, 1967). Examples of integral dimensions would be pitch and loudness; a tone cannot exist without both of these dimensions.…”
Section: Relevant Variablesmentioning
confidence: 99%
“…The chief concern of that research has been to determine whether information about several dimensions is processed simultaneously or one dimension at a time (Egeth, 1966;Lindsay & Lindsay, 1966;Neisser, 1967;Nickerson & Feehrer, 1964). It seemed worthwhile to attempt to extend this analysis to the absolute .94…”
Section: Methodsmentioning
confidence: 99%
“…There have been a number of studies reported that were concerned with the question of whether the processing of separable attributes (e.g., shape and size) of a single stimulus can be processed simultaneously or must be processed serially (e.g., Biederman & Checkosky, 1970;Downing & Gossman, 1970;Egeth, 1966;Hawkins, 1969;Lindsay & Lindsay, 1966;Nickerson, 1967;Saraga & Shallice, 1973). The tasks in these earlier studies were usually comparison tasks wherein a subject reported whether multiattribute items were the same as, or different from, a memorized target item.…”
Section: Processing Of Multi-dimensional Stimulimentioning
confidence: 99%
“…Items could differ in terms of a single attribute or many attributes. Most investigators concluded that multiple attributes could be processed simultaneously (but see Egeth, 1966, andLindsay &Lindsay, 1966).…”
Section: Processing Of Multi-dimensional Stimulimentioning
confidence: 99%